Antioxidative Properties of Decoction of Pistacia atlantica Desf. Leaves - Peksel, Aysegul (Asian Journal of Chemistry, 2010)
The antioxidative properties of decoction of leaves from P. atlantica Desf. were determined as the radical scavenging activity, as the total antioxidant activity, as reducing power, as chelating abilities on metallic ions, as hydrogen peroxide scavenging activity. In addition, preliminary phytochemical screening, total phenolics, anthocyanin, total chlorophyll and total carotenoid contents were also studied. The results were compared with natural and synthetic antioxidants, e.g., α-tocopherol, trolox, butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA). The decoction prepared from the leaves of Pistacia atlantica Desf. is good sources of compounds with antioxidant properties while extract exhibited strong reducing power, free radical scavenging activity and total antioxidant activity.